DESIGN IMPLEMENTASI KECERDASAAN BUATAN PADA CHATBOT LINE DALAM PERMAINAN TEBAK ANGKA - Mayatopani Hendra; Nurdiana Handayani (Joutica, 2019)
Information technology provides a new change in the increasingly diverse world of games with play games that are fun when played and content is given in such an interesting way in packaging, artificial intelligence in games can provide interactive play between users and the system adds to the playing experience, the game world has entered Social media applications are some of the applications that were originally formed for relationships and now add realtime gaming features to play with friendships that have been added to the application. The game that will be designed using the chatbotline on social media Line starts from the game play flow about guessing a number that will later come out whether the guess results from the user are correct or wrong based on artificial intelligence and the highest score is the winner. The results obtained from game design provide the user experience for interaction in playing or with other users to increase the excitement in using social media.